Lung function in children with juvenile idiopathic arthritis: A cross‐sectional analysis. Issue 8 (17th May 2019) - Attanasi, Marina; Lucantoni, Marta; Rapino, Daniele; Petrosino, Marianna I.; Marsili, Manuela; Gasparroni, Giorgia; Di Filippo, Paola; Di Pillo, Sabrina; Chiarelli, Francesco; Breda, Luciana
Abstract: Aim: We measured respiratory parameters in children with juvenile idiopathic arthritis (JIA) without clinical signs of respiratory involvement and assessed the influence of methotrexate (MTX) treatment and disease activity on lung function. Methods: In 49 JIA children and 70 controls lung volumes by spirometry and body plethysmography, and lung diffusion for carbon monoxide (DLCO) with single‐breath technique were evaluated. Results: DLCO was significantly different between JIA children and controls ( P  = .01), whereas no differences were found in flow expiratory volume in 1 second (FEV1 ), forced vital capacity (FVC), forced expiratory flow at 25% to 75% of FVC (FEF25‐75 ), peak expiratory flow, total lung capacity, and residual volume. After dividing study JIA patients according to MTX treatment, a significant difference in DLCO was found among JIA patients treated with MTX and those treated with other drugs and controls ( P  < .001). A significant difference in DLCO was also found among JIA patients with active disease and those with inactive disease and controls ( P  = .003). Analysis of covariance showed a weak independent effect of MTX therapy on DLCO after adjusting for sex and height ( P  = .04). Furthermore, a negative correlation of DLCO with MTX cumulative dose and MTX treatment duration ( r  = −.58, P  = .006; r  = −.68, P  = .001, respectively) was found, whereas there was no correlation between DLCO and disease activity ( r  = −.10; P  = .51). Conclusions: In JIA children MTX treatment seems to have a dose‐dependent effect on lung function. For this reason in these patients, a regular assessment of lung function, especially with DLCO evaluation, is recommended.